Doing Contrariness: Therapeutic Talk-In-Interaction in a Single Therapy Session With a Traumatized Child - Buchholz, Michael B.; Buchholz, Timo; Wülfing, Barbara (Frontiers in Psychology, 2021)
Conversation analysis (CA) of children-adult—interaction in various contexts has become an established field of research. However, child therapy has received limited attention in CA. In child therapy, the general psychotherapeutic practice of achieving empathy faces particular challenges. In relation to this, our contribution sets out three issues for investigation and analysis: the first one is that practices of achieving empathy must be preceded by efforts aiming to establish which kind of individualized conversation works with this child (Midgley, 2006). Psychotherapy process researchers in adult therapy (Stiles, Hill, & Elliott, 2015) have found that therapists “invent” a new therapy for each patient (Norcross & Wampold, 2018). The second issue is that it can be difficult for adults to understand the ways in which children express their conflicts and issues. In particular, play activities in therapy, e.g. with dolls, can open up additional scenarios of interaction. The play scenario can be used to disclose unformulated problems masked in everyday and family interactions. The third issue is how to respect the child’s higher degree of vulnerability, compared to adult patients. How is it communicated and dealt with in therapy? We present an interaction analysis of a single case study of the first 20 mins of a child therapy session with an adopted girl aged four years brought to treatment because of “unexplainable rage”. The session was videotaped; parents granted permission. We analyze this session using an applied version of CA. In our analysis, we describe “doing contrariness”, departing from an observation in Tarplee (1996), as a conversational practice producing epistemic and affiliative disruptions, while “avoiding doing contrariness” and “remedying contrariness” are strategies for preserving or restoring the affiliative dimension of a relationship (in child therapy). We show how these practices operate in various modes and how they are used by both parties in our case study to variously aid and impede the achievement of empathy and understanding.